Response to Combination Therapy of Interferon Alfa-2b plus Ribavirin in Hispanics with Chronic Hepatitis C - Muñoz, Humberto; Arroyo, Javier; Torres, Esther; De Jesús-Monge, Wilfredo E.; Chinea, Betty; González, Henry; Aponte, Néstor; Guzmán, Aileen; Rivera, Cynthia; Rodríguez, Federico; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2013)
Objective. To evaluate the response rate of Hispanics with chronic hepatitis C to combination therapy of interferon alfa-2b plus ribavirin and to assess its adverse events. Background. Hepatitis C virus may lead to chronic infection and multiple complications. Response to combination therapy of interferon plus ribavirin has been studied in many populations. African Americans have been found to have a lower response rate than Caucasians. However, little data exist for Hispanics. Methods. Hispanic patients from Puerto Rico with chronic hepatitis C were eligible for the study between November 1997 and February 2000. The Institutional Review Boards of the participating institutions approved the study. Written informed consents were obtained. Combination therapy was given for 48 weeks and patients were followed for 24 weeks after treatment. Analysis of response to therapy was performed in an intention-to-treat basis. Results. The most frequent adverse event was anemia (89%), associated to ribavirin. Sustained response was 23% for naive patients, 45% for relapsers, and 8% for non-responders to previous interferon monotherapy (p < 0.001). Data to analyze response was not available in 27% of patients. Hispanic patients had a low response rate to combination therapy. Conclusions. Response rates to combination therapy for Hispanic naive and previously non-responder patients are lower than in other reported populations. This may be due to a high prevalence of genotype 1 in Puerto Rico, which is associated to poor response. The higher response rate of relapsers, similar to those reported previously, was expected since these patients showed a previous response to interferon monotherapy. Ethnic factors may play a role in the response to therapy and should be further studied to determine proper treatment strategies for this population.